Fuzzy approach for predicting combined effect of variables affecting consumer food preferences. (31st March 2021) - Baskar, R.
Predicting the behaviour of consumers is always a challenge for marketers. Consumers are moved by various factors to make choices of food. This paper provides a framework for predicting consumer food preferences using fuzzy approach which considers uncertainties in predicting the combined effect of factors which affect the consumer food preferences. Advantage of using a fuzzy approach is its power to interpret the semantics of human assessment. In predicting the effect of variables affecting consumer food preferences, three variables which have significant impact were identified, confirming our literature review. A FIS model is tested on the factors which affect the consumer's food preferences and the results are discussed. Among the factors, the consumer's attitude is found to have a major impact in determining the food preferences, and using the fuzzy approach gives an understanding on the intensity of the role of these variables in predicting the consumer food preferences. The results are useful for businesses which design products based on consumer food preferences.